PENGARUH PEMBERIAN REWARD DAN ICE BREAKING TERHADAP MINAT BELAJAR MATEMATIKA SISWA KELAS III MIS AL-HADI II KECAMATAN KASIHAN - Cahyasetiaji, Ardi; Bahtiyar Heru Susanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Interest in learning is the entry point of any meaningful instructional process, yet third-grade mathematics classrooms are frequently dominated by one-way lecturing that leaves pupils drowsy and disengaged. This study examines the effect of giving rewards and ice breaking on students' interest in learning mathematics at MIS AlHadi II, Kasihan District. A quantitative approach with a quasi-experimental design of the intact-group comparison type was applied. Through purposive sampling, 46 third graders were involved: class III-A (23 pupils) as the experimental group and class III-B (23 pupils) as the control group. Data were gathered through observation, interviews with the homeroom teachers, and a four-point Likert scale questionnaire of 26 valid items (Cronbach's Alpha 0.883). Analysis proceeded through instrument testing, prerequisite testing (normality, homogeneity, linearity), and hypothesis testing using simple and multiple linear regression with SPSS Statistics 23. The findings show that rewards significantly affect interest in learning mathematics (Sig. 0.000; R square 0.275 or 27.5%), ice breaking exerts a stronger effect (Sig. 0.000; R square 0.571 or 57.1%), and both variables jointly explain 58.6% of the variance in learning interest (Sig. 0.000; R square 0.586). The mean score of the experimental class rose from 85 to 88 across two meetings, while the control class moved from 78 to 80. The marginal contribution of rewards once ice breaking is present turns out to be small, suggesting that physical and emotional reengagement matters more than material appreciation for young learners.